2001
DOI: 10.1108/eum0000000007075
|View full text |Cite
|
Sign up to set email alerts
|

A theory of the task‐based information retrieval process: a summary and generalisation of a longitudinal study

Abstract: A theory of the task-based information retrieval process: a summary and generalisation of a longitudinal study Pertti Vakkari Article information:To cite this document: Pertti Vakkari, (2001),"A theory of the task-based information retrieval process: a summary and generalisation of a longitudinal study"Access to this document was granted through an Emerald subscription provided by emerald-srm:463575 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
243
1
4

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 243 publications
(256 citation statements)
references
References 15 publications
4
243
1
4
Order By: Relevance
“…Studies from the 1980s defined novices as those who had not undertaken independent online searching, or had undertaken a beginners' course in information seeking, (Howard, 1982;Harter, 1984) and defined expertise in terms of the number of searches carried out over a certain period, for example a month, (Howard, 1982) or for a certain time prior to the study (Harter, 1984). Later studies have followed a student group from relative inexperience to the attainment of far greater expertise (Whitmire, 2002;Vakkari, 2001;Wilson et al 2002;Kuhlthau, 2004;Spink et al, 2002a and b), and thus the experts and novices are, in effect, the same group of participants at different stages of development. Librarians have also been used as an expert group from whom lessons may be learnt for the design of digital library systems (Fields et al, 2004).…”
Section: Experts and Novicesmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies from the 1980s defined novices as those who had not undertaken independent online searching, or had undertaken a beginners' course in information seeking, (Howard, 1982;Harter, 1984) and defined expertise in terms of the number of searches carried out over a certain period, for example a month, (Howard, 1982) or for a certain time prior to the study (Harter, 1984). Later studies have followed a student group from relative inexperience to the attainment of far greater expertise (Whitmire, 2002;Vakkari, 2001;Wilson et al 2002;Kuhlthau, 2004;Spink et al, 2002a and b), and thus the experts and novices are, in effect, the same group of participants at different stages of development. Librarians have also been used as an expert group from whom lessons may be learnt for the design of digital library systems (Fields et al, 2004).…”
Section: Experts and Novicesmentioning
confidence: 99%
“…Novices tend now to be defined as those who are unfamiliar with a certain digital library (Blandford et al, 2001) or who, as in our study, have done little independent information seeking in an academic context. Vakkari (2001), for example, even regards MA students who have gained a first degree in Information Studies as relative novices in information seeking. The study reported here provides further evidence that a first degree in an information discipline is not a passport to search expertise.…”
Section: Experts and Novicesmentioning
confidence: 99%
See 3 more Smart Citations